Testing the hormesis hypothesis on motor behavior under stress - Voigt, Laura; Hill, Yannick; Frenkel, Marie Ottilie (Applied ergonomics, 2024)
While much research has focused on the deleterious effects of stress on goal-directed behavior in recent decades, current views increasingly discuss growth under stress, often assuming dose-dependent effects of stress in a curvilinear association. This is based on the concept of hormesis, which postulates a strengthening effect of stress at low-to-moderate doses. Leveraging this approach, hormetic curves indicate under which stress dose an individual is able to maintain or even increase goal-directed behavior. The present study aimed to test the hormetic effect of low-to-moderate stress on tactical movement performance in the context of police operational scenarios in virtual reality. In teams of three to four, 37 riot police officers had to search a building for a potentially aggressive perpetrator in three scenarios with escalating stress potential (i.e., increasing weapon violence and number of civilians). Tactical movement performance as behavioral response was quantified by the sample entropy of each officer's velocity derived from positional data. To account for inter-individuality in response to the scenarios, we assessed self-reported stress, anxiety, mental effort, and vagally mediated heart rate variability. Specifically, we tested the quadratic associations between tactical movement performance and stress parameters, respectively. Random-intercept-random-slope regressions revealed neither significant linear nor quadratic associations between any of the stress parameters and performance. While we did not find evidence for hormesis in the present study, it stimulates theoretical discussions about the definition of “baseline” functioning and how the understanding of hormesis can move from psychological to behavioral adaptations to stressors.
Gesehen am 29.07.2024